Pengaruh Relationship Quality Terhadap Loyalitas Nasabah KPR Subsidi Pada Bank PT. Bank Tabungan Negara (Persero) Tbk Cabang Padang - Niken Mardhatillah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The main goal of the bank is to make customers loyal to the bank. For this reason, every bank must always pay attention to the needs and desires of customers and try to fulfill their expectations in a better and more satisfying way than other competing banks do. Loyal customers are a banking company's asset, therefore banking companies must build better relationships with each of their customers, namely by building customer loyalty and maintaining and maintaining them so that they do not turn to other banking companies.